Effects of TPMT, NUDT15, and ITPA Genetic Variants on 6-Mercaptopurine Toxicity for Pediatric Patients With Acute Lymphoblastic Leukemia in Yunnan of China - Mao, Xiaoyan; Yin, Runxiu; Sun, Gaoyuan; Zhou, Yan; Yang, Chunhui; Fang, Chunlian; Wu, Yuhong; Cui, Tingting; Liu, Li; Gan, Jiaxin; Tian, Xin (Frontiers in Pediatrics, 2021)
Background: 6-Mercaptopurine (6-MP) is the cornerstone of current antileukemia regimen and contributes greatly to improve the survival of pediatric acute lymphoblastic leukemia (ALL) patients. However, 6-MP dose-related toxicities limit its application. TPMT, NUDT15, and ITPA are pharmacogenetic markers predicting 6-MP-related toxicities, but their genetic polymorphisms differ from those of ethnic populations. In Yunnan province, a multiethnic region of China, we had no genetic data to predict 6-MP toxicities. In this study, we evaluated the most common variants involved in 6-MP metabolism—TPMT*3C (rs1142345), NUDT15 c.415C>T (rs116855232), and ITPA c.94C>A (rs1127354) variants—in our cohort of pediatric ALL patients. Methods: A total of 149 pediatric ALL patients in the Affiliated Children's Hospital of Kunming Medical University (Yunnan Children's Medical Center) from 2017 to 2019 were enrolled in this retrospective study. We assessed the TPMT*3C (rs1142345), NUDT15 c.415C>T (rs116855232), and ITPA c.94C>A (rs1127354) frequencies and evaluated association between genotypes and 6-MP toxicities, 6-MP dose, and event-free survival (EFS) in these ALL patients. Results: The allele frequencies of TPMT*3C (rs1142345), NUDT15 c.415C>T (rs116855232), and ITPA c.94C>A (rs1127354) were 1.34%, 14.43%, and 18.79%, respectively. Only NUDT15 c.415C>T (rs116855232) was strongly associated with 6-MP toxicity and 6-MP tolerable dose. NUDT15 c.415C>T was related to leukopenia, p = 0.008, OR = 2.743 (95% CI: 1.305–5.768). The T allele was significantly correlated with 6-MP tolerable dose, dose of NUDT15 c.415C>T wild genotype CC 39.80 ± 1.32 mg/m2, heterozygotes CT 35.20 ± 2.29 mg/m2, and homozygotes TT 18.95 ± 3.95 mg/m2. 6-MP tolerable dose between CC and TT had a significant difference, p = 0.009. Between CC and CT, and CT and TT, they had no significant difference. EFS showed no significant difference among NUDT15 c.415C>T genotypes. Conclusion:NUDT15 c.415C>T (rs116855232) was an optimal predictor for 6-MP toxicity and tolerable dose in pediatric ALL patients from Yunnan province, a multiethnic region in China, and would play an important role in precise therapy for ALL.